If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2x = 6x + -9 Combine like terms: 5x + 2x = 7x 7x = 6x + -9 Reorder the terms: 7x = -9 + 6x Solving 7x = -9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7x + -6x = -9 + 6x + -6x Combine like terms: 7x + -6x = 1x 1x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 1x = -9 + 0 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| 13=3b+22 | | 6x+1=12x+17 | | 17x+12x-4=42 | | c(c-4)=21 | | 15s^3+25s^2-60s= | | -2m+4m+5=-3 | | 16-4t=4t | | 9x^2+28x+52=0 | | 17x-2(3x+4)=20 | | 2(6+3)= | | -13=x-7 | | x^2-24x+24=0 | | .15x-3.2=.5(x-5) | | 3x-4=2(7-x) | | 48-4t=4t | | 3(y-7)= | | (4x-2)=-1+2x | | 5-3(2x+9)=50 | | 0.4(x+90)+0.2x=45 | | X^2+4x-169=0 | | -5x+6=9-6x | | 9+5a=-26 | | t-22=-23 | | 8n-8=5n+7 | | -16t^2+40t-65=0 | | -16t^2+40t+65=0 | | 1.5(4d-2)=d+5 | | 4x-2=-6+5x | | 2x^2-48x+48=0 | | n-3=17-4n | | 7x+10=5x+6 | | 2+2y=3 |